The Effect of Malaysia Goods & Services Tax (GST) to the construction industry - Intan Nursyafiqah, Mohamed Hissam (2016)
The purpose of this study is to identify the perception of the construction industry towards the implementation of the Goods and Services Tax (GST). The others purpose of this research is to investigate the pricing effect from the perspectives of the construction industry. According to Malaysia Customs, the Goods and Services Tax (GST) is a value added tax in Malaysia. GST is levied on most transactions in the production process, but is refunded to all parties in the chain of production other than the final consumer. From this research, the independent variables are developer, consultant and the contractor while for dependent variable is the Goods and Services Tax (GST). The cost such as tax on construction cost, material cost, labor cost and management cost in construction industry has been discussed in this research.